Oral Health Behaviors of Elementary School Children In Bandung City - Grace Monica; Ivana Abigayl; Ignatius Setiwan (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Dental health behaviors established from an early age, such as toothbrushing habits, use of fluoride toothpaste, parental supervision, dental visits, and levels of dental treatment anxiety, play a crucial role in preventing caries. Objective: This study aimed to evaluate five indicators of oral health behavior among elementary school students in Bandung City and to compare behavioral differences between students attending public and private schools. Methods: A cross-sectional survey was conducted on 4,721 students, aged 6-9 years, from 14 schools. Data were collected using a questionnaire completed with assistance from dental students. Data were analyzed using the chi-square test with SPSS. Results and Discussion: The majority of students brushed their teeth twice daily (70.7%) and used fluoride toothpaste (86.9%). Parental supervision during toothbrushing was more common in private schools (18% vs. 8%). 35.3% of students had never visited a dentist, with a higher proportion in public schools (38% vs. 27%). Fear of the dentist was reported by 41.9% of students, while 94.9% stated that they were concerned about their oral health. Significant differences between public and private schools were found in toothbrushing frequency, parental assistance, fluoride use, and dental visit frequency (p < 0.05). Conclusion: Although oral health awareness among elementary school children in Bandung City is relatively high, behavioral gaps remain, particularly regarding dental visits and parental supervision. School-based interventions involving teachers and parents, combined with interactive education and reinforcement of preventive behaviors, are needed to optimize children’s oral health sustainably.